Prevalence, Determinants, and Consequences of Vestibular Hypofunction. Results From the KORA-FF4 Survey - Grill, Eva; Heuberger, Maria; Strobl, Ralf; Saglam, Murat; Holle, Rolf; Linkohr, Birgit; Ladwig, Karl-Heinz; Peters, Annette; Schneider, Erich; Jahn, Klaus; Lehnen, Nadine (Frontiers in Neurology, 2018)
Objective Uni- or bilateral vestibular hypofunction (VH) impairs balance and mobility, and may lead to injuryand to disability. The extent of this problem in the general population is still unknown. Objective of this study was to determine the prevalence, determinants and consequences of VH in the general population. Methods Data originates from the cross-sectional second follow-up (FF4) in 2013/14 of the KORA (Cooperative Health Research in the Region of Augsburg)-S4 study (1999-2001) from Southern Germany. This was a random sample of the target population consisting of all residents of the region aged 25 to 74 years in 1999. We included all participants who reported moderate or severe vertigo or dizziness during the last 12 months and a random sub-sample of participants representative for the general population without vertigo or dizziness during the last 12 months were tested. VH was assessed with the Video-Head Impulse Test (vHIT). Trained examiners applied high-acceleration, small-amplitude passive head rotations (“head impulses”) to the left and right in the plane of the horizontal semicircular canals while participants fixated a target straight ahead. During head impulses, head movements were measured with inertial sensors, eye movements with video-oculography (EyeSeeCam vHIT). Results A total of 2279 participants were included (mean age 60.8 years, 51.6% female), 570 (25.0%) with moderate or severe vertigo or dizziness during the last 12 months. Of these, 450 were assessed with vHIT where 26 (5.8%) had unilateral VH, and 16 (3.6%) had bilateral VH. Likewise, 190 asymptomatic participants were tested. Of these 5 (2.6%) had unilateral VH, and 2 (1.1%) had bilateral VH. Prevalence of uni- or bilateral VH among tested symptomatic participants was 2.4% in those < 48 years, and 32.1% in individuals aged 79 and over. Age-adjusted prevalence was 6.7% (95% CI 4.8%; 8.6%). VH was associated with worse health, falls, hearing loss, hearing impairment and ear pressure. Conclusion VH may affect between 53 and 95 million adults in Europe and the US. While not all affected persons will experience the full spectrum of symptoms and consequences, adequate diagnostic and therapeutic measures should become standard of care to decrease the burden of disease.